Research on the Chinese Path to Modernization in History, Key Topics, and Outlook: A CiteSpace-based Bibliometric Analysis - Wang, Linmei; Yang, Huiru (Contemporary social sciences (Chengdu), 2023)
In the speech delivered at the centenary celebration of the Communist Party of China (CPC), Xi Jinping, general secretary of the Communist Party of China (CPC) Central Committee, made important remarks on the "Chinese path to modernization." This term represents the latest achievement China has scored in adapting Marxism to the Chinese context and the needs of the times. It has set the course as China embarks on a new journey of building a strong socialist country with Chinese characteristics and achieving national rejuvenation. Drawing on CiteSpace, we conducted a visualized bibliometric analysis of literature on the Chinese path to modernization by searching the CNICI database using subject terms such as "Chinese modernization, Chinese path to modernization, and Chinese-style modernization." The findings reveal that: (a) Research on the Chinese path to modernization has gone through three stages: initial establishment, pioneering exploration, and comprehensive in-depth development, (b) Existing literature has covered the four key topics associated with the Chinese path to modernization, namely its essence, goal, methodology, and pioneering achievements, (c) Future research may focus on building up China's strength in agriculture, developing the digital economy, modernizing China's system and capacity for governance, and establishing a unique socialist discourse system for Chinese modernization.